2014
DOI: 10.1891/1078-4535.20.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Seeing the Forest and the Trees: Increasing Nurse Practitioner Students ‘Observational and Mindfulness Skills

Abstract: Accurate, objective observation is a critical component of clinical diagnosis and patient management, which in turn is essential for successful diagnostic reasoning by advanced practice nurses. The purpose of this quasi-experimental study was to enhance nurse practitioner students' observation and reflective thinking skills using Looking Is Not Seeing, a reflective practice/experiential learning technique that uses art objects to teach observation (Pellico, Friedlaender, & Fennie, 2009). Students' posttest obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…108,109 Nursing literature is replete with information on educational strategies to facilitate reasoning in nursing students. 89,108,[110][111][112] Downloaded from https://academic.oup.com/ptj/advance-article-abstract/doi/10.1093/ptj/pzy148/5212793 by Chapman University Library user on 04 December 2018…”
Section: [Hd2]synopses Of Clinical Reasoning By Disciplinementioning
confidence: 99%
“…108,109 Nursing literature is replete with information on educational strategies to facilitate reasoning in nursing students. 89,108,[110][111][112] Downloaded from https://academic.oup.com/ptj/advance-article-abstract/doi/10.1093/ptj/pzy148/5212793 by Chapman University Library user on 04 December 2018…”
Section: [Hd2]synopses Of Clinical Reasoning By Disciplinementioning
confidence: 99%
“…A total of around 300 articles were reviewed in detail. After applying the aforementioned inclusion and exclusion criteria, the literature search yielded 12 studies, [26][27][28][29][30][31][32][33][34][35][36][37] as listed in Table 1. Thereafter, 3 of these 12 studies 28,31,37 were found by manual search and missed by search results of the aforementioned review studies.…”
Section: Resultsmentioning
confidence: 99%
“…The identified training approaches are: visual thinking strategy, [29,34] visual reinforcement, [30] visual literacy, [31] Looking Is Not Seeing pedagogy [32,33] and training the clinical eye. [35] The training approaches follow two main types of training principles: training the eye for deep seeing and guiding the eye.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the seven studies, six used a static display of patient images [29,[31][32][33][34][35] and improvements were then reported when there was an increase in the number of details provided by the participant, the number of words used by the student to describe the image, and the number of accurate observations made. [29,[31][32][33][34][35] Jarodzka et al [30] reported improvement in students' ability to visually search for clues and interpret the findings (see Table 1). It appeared that the evaluation was conducted immediately after finishing the training sessions and there was no follow up to evaluate if these improvements were consistently transferred to the authentic practice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation